1978
DOI: 10.2134/agronj1978.00021962007000020013x
|View full text |Cite
|
Sign up to set email alerts
|

Field Response of Four Tropical Legumes to Lime and Superphosphate1

Abstract: The generalization is often made that tropical legumes show little or no response to lime, even in acid soils low in Ca. Phosphorus responses, however, are generally observed. The effect of lime in an acid, virgin spodosol (Oldsmar fs) in southern Florida plots was investigated. Significant yield responses to lime and P were observed. Maximum total annual dry matter production of centro (Centrosema pubescens Benth.), desmodium (Desmodium heterocarpon DC.), stylo (Stylosanthes guyanensis Swartz), and ‘Siratro’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Olsen & Moe (1971) and Bogdan (1977) state that no response can be expected from liming. However, Snyder, Kretschmer & Sartain (1978) recommend liming, but are of the opinion that liming beyond the optimum rate could seriously reduce production of Stylosanthes guianensis. According to Spain (1975) tropical legumes realise maximum yields with only 150 kg CaC0 3 equivalent ha-I • Calcium is often supplied with the P source, thereby concealing the response to lime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olsen & Moe (1971) and Bogdan (1977) state that no response can be expected from liming. However, Snyder, Kretschmer & Sartain (1978) recommend liming, but are of the opinion that liming beyond the optimum rate could seriously reduce production of Stylosanthes guianensis. According to Spain (1975) tropical legumes realise maximum yields with only 150 kg CaC0 3 equivalent ha-I • Calcium is often supplied with the P source, thereby concealing the response to lime.…”
Section: Discussionmentioning
confidence: 99%
“…t 'Mannetjie, O'Conner & Burt (1978) concluded that the addition of lime to S. guianensis grown on an acid soil can lead to reduced yields owing to an induced zinc deficiency. In the study of Snyder et al (1978), where S. guianensis responded significantly to liming, Zn was added to the soil.…”
Section: Discussionmentioning
confidence: 99%
“…At low pH, AP+ is phytotoxic, nodulation is inhibited, and Ca and Mo deficiencies occur (Fox and Kang, 1977;Carvalho et al, 1981). Liming of tropical soils has been a common practice to alleviate problems associated with low pH (Snyder et al, 1978;Andrew and Johnson, 1976;Munns et al, 1977;Munns and Fox, 1977). Unfortunately, the tendency to overtime is common and the final results are not always favorable.…”
mentioning
confidence: 99%